Real time monitoring and control in water distribution systems for improving operational efficiency. Issue 25 (6th January 2016) - Kara, Selami; Karadirek, I. Ethem; Muhammetoglu, Ayse; Muhammetoglu, Habib
Abstract: The global water sector faces challenges to maintain safe, healthy, and adequate water supply to its consumers. Control of water quality and quantity by real-time monitoring (RTM) plays an important role in the management of water distribution systems (WDSs) and protection of consumers' health. RTM could be used for monitoring and analyses of water quality parameters to ensure its suitability for drinking. Additionally, RTM system warns operators to stop water supply to save water and minimize risks when needed. WDS of Antalya City is monitored and controlled by an advanced RTM and Supervisory Control and Data Acquisition (SCADA) system. Integrated RTM–SCADA system monitors and controls both hydraulic and water quality parameters to improve the WDS's operational efficiency. The system automatically controls pumps and valves and it has security alarms if any of the monitored water quality parameters fail to comply with the drinking water quality standards. This feature helps to protect WDS from the adverse impacts of an intentional or unintentional contamination event. Furthermore, RTM system is very helpful to detect water losses. Integrated RTM–SCADA system in WDSs provides many operational benefits (improved water quality, decreased operational costs, reduced customer complaints, reduction in water losses, and modeling capability) but it requires a good management system to assess huge amount of collected data.